Regularized Methods of Noisy Signals Differentiation in Real Time - Sterten, Jo; Furtat, Yu.O. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2017)
One particular case of solving the problem of interpreting observations is considered, when the instrument function of the measuring transducer is a pure integrator. In this case, the problem of interpretation is reduced to differentiating the output signal of the measuring transducer. Рассмотрен один частный случай решения задачи интерпретации наблюдений, когда аппаратная функция измерительного преобразователя является чистым интегратором. При этом задача интерпретации сводится к дифференцированию выходного сигнала измерительного преобразователя.